Heilige Helden: Zu den Spielarten einer Metapher und ihrer musikalischen Artikulation in den Historiae des Mittelalters - Hankeln, Roman (De musica disserenda, 2015)
It is significant for medieval Latin liturgical texts (including plainchant texts) that early Christian authors adopted the language of war and heroism in a metaphorical sense to describe the character and behavior of the saints, and especially of martyrs. This paper investigates the various modes of this heroic metaphor in the textual and musical representation of saints in medieval saints’ offices, the historiae, by analyzing five examples taken from the historiaein honor of St. Fides of Agen (Aquitaine, eleventh c.), St. Oswald of Northumbria (England, eleventh c.), and St. Charlemagne (Aachen, twelfth c.). It shows how the topic of “heroism” is articulated through analogies between textual and musical structures.